2016
DOI: 10.1073/pnas.1607506113
|View full text |Cite
|
Sign up to set email alerts
|

How the toughness in metallic glasses depends on topological and chemical heterogeneity

Abstract: To gain insight into the large toughness variability observed between metallic glasses (MGs), we examine the origin of fracture toughness through bending experiments and molecular dynamics (MD) ngineering ceramics are strong, with high yield strength, but suffer from brittleness. In contrast, crystalline metals tend to have high fracture toughness because dislocation motion promotes plastic deformations that suppress cracks propagations, but concomitantly this dislocation motion reduces yield strength. Metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 30 publications
(60 reference statements)
2
21
2
Order By: Relevance
“…Hence, the small STZs weaken the shear capability of the MG, i.e., the plastic flow, which is consistent with the observations in Figure 6 and the evolutions of the G/B and ν values with the temperature. Recently, An et al [27,28] found that a low toughness in MG indicated a decreased activation energy barrier for the cavitation event. In our present study, the small STZs of the MG at cryogenic temperature indicate that the thermal activation of the plastic flow is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the small STZs weaken the shear capability of the MG, i.e., the plastic flow, which is consistent with the observations in Figure 6 and the evolutions of the G/B and ν values with the temperature. Recently, An et al [27,28] found that a low toughness in MG indicated a decreased activation energy barrier for the cavitation event. In our present study, the small STZs of the MG at cryogenic temperature indicate that the thermal activation of the plastic flow is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…After we obtained the amorphous structures in DFT-MD simulations, we performed geometry relaxation using DFT to relax the internal stress. Then we performed the structural analyses such as RDF and Voronoi analysis 53 on these relaxed structures. The radial distribution function (RDF) describes how density varies as a function of distance from a reference particle.…”
Section: Methodsmentioning
confidence: 99%
“…A wide distribution of stacking fault energy in HEAs and the atomic level heterogeneity foster deformation-induced martensitic transformation, 19 leading to outstanding mechanical properties and improved cryogenic performance; such small-scale level heterogeneity has also been adopted in amorphous metals for better toughness. 20,21…”
Section: Introductionmentioning
confidence: 99%